Pengaruh Brand Image, Product Quality dan Lifestyle terhadap Keputusan Pembelian: Studi pada Distro Luxurious Dalung - Anggreni, Ni Made Sintia; Putri Trarintya, Mirah Ayu; Yayati Wilyadewi, Ida I Dewa Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Appropriate market segmentation is used to maintain consumer purchasing decisions from teenagers and adults as a complement to secondary needs, so that business people must think and find new ideas to maintain their business so that they are able to compete to achieve the expected goals. Sales experienced very fluctuating increases and decreases in the 2022-2023 period at the Luxurious Dalung Distro and only experienced an increase of 1.24%, causing researchers to be interested in conducting research regarding purchasing decisions. The aim of this research is to determine the influence of brand image, product quality and lifestyle partially and simultaneously on purchasing decisions. The research method is quantitative. The sample used was 100 respondents. Purposive sampling technique for determining the sample. Data analysis techniques are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, T Test and F Test. The results of this research show that brand image has a significant positive effect on purchasing decisions, product quality has a significant positive effect on purchasing decisions, and has a significant positive effect on purchasing decisions. Brand image, product quality and lifestyle have a significant positive effect on purchasing decisions. The magnitude of the influence of the independent variable on purchasing decisions is 66.7%.